MEDICINE UNDER THE KHOREZMSHAHS - Muminova Oftobkhon (Journal Park Publishing, 2023)
In the Middle Ages, science and culture reached a high level in the countries of Central Asia rose. Science centers, dorilfununs, madrasahs in big cities was established. Many scientists, philosophers, representatives of literature and art they matured. These scientists and scholars in various fields of science and culture created immortal works. They are invaluable to world science and culture they became masterpieces. Firdausi's Shahnama, Ibn Sina's "Laws of medicine", ghazals of Sheikh Sa'di, Alisher Navoi "Hamsa" is one of them. In the process of such a general rise medicine also developed. In cities and large populated areas hospitals, pharmacies were established. Medical knowledge in big cities countries were established. In addition, madrasahs are also secular Among the sciences, medical science was also taught. If there are not many of them well-educated judges also prepared.
Keywords: Medical Collection, research work, divine, statesmen, treatment, prevention.